2019
DOI: 10.7717/peerj.6795
|View full text |Cite
|
Sign up to set email alerts
|

Likes, comments, and shares of marine organism imagery on Facebook

Abstract: Several calls to action urge scientists and science communicators to engage more with online communities. While these calls have been answered by a high percentage of scientists and science communicators online, it often remains unclear what are the best models for effective communication. Best practices and methods for online science communication can benefit from experimental and quantitative research addressing how and when users engage with online content. This study addresses with quantitative and predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 53 publications
(65 reference statements)
2
23
0
1
Order By: Relevance
“…In recent years, increased interest for their commercial value inspired gastronomy (Mouritsen and Styrbæk, 2018 ; see also: Sörensen and Mouritsen, 2019 and Cephs & Chefs: https://www.cephsandchefs.com/ ). In addition, social media provided access to specialized information and growing interest in interdisciplinary academic fields, and images and videos where cephalopods represent a great example (Nakajima et al, 2018 ; McClain, 2019 ). Together with fishes, images of cephalopods have been “liked” more than other organisms (including sharks) on social media platforms (McClain, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, increased interest for their commercial value inspired gastronomy (Mouritsen and Styrbæk, 2018 ; see also: Sörensen and Mouritsen, 2019 and Cephs & Chefs: https://www.cephsandchefs.com/ ). In addition, social media provided access to specialized information and growing interest in interdisciplinary academic fields, and images and videos where cephalopods represent a great example (Nakajima et al, 2018 ; McClain, 2019 ). Together with fishes, images of cephalopods have been “liked” more than other organisms (including sharks) on social media platforms (McClain, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, social media provided access to specialized information and growing interest in interdisciplinary academic fields, and images and videos where cephalopods represent a great example (Nakajima et al, 2018 ; McClain, 2019 ). Together with fishes, images of cephalopods have been “liked” more than other organisms (including sharks) on social media platforms (McClain, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As of Fall 2019, 6,500+ accounts followed the March Mammal Madness Facebook page and the day the 2019 tournament bracket dropped the FB post organically reached 43,000+ Facebook newsfeeds from user engagement. These social media engagement numbers for followers, shares, and retweets indicate that tournament content is broadly reaching public audiences ( Côté and Darling, 2018 ; McClain, 2019 ). Moreover, social media engagement around natural world content has been associated with increased donations to conservation campaigns ( Lenda et al, 2020 ) and long-term changes in species awareness ( Fernández-Bellon and Kane, 2020 ).…”
Section: Emergent Community: Public Scientists and Institutionsmentioning
confidence: 99%
“…Comprehensive roadmaps of successful SciComm initiatives, campaigns, and programs have been infrequently described in the scholarly literature. Early and recent reports, however, have demonstrated that memes, images, activities, and dynamic content from scientists are associated with increased learner and public interest, competencies, donations, and enthusiasm for nature ( Moskal et al, 2007 ; Hone et al, 2011 ; McClure et al, 2020 ; McClain, 2019 ; Lenda et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The power of public opinion also means that the less-well-known or less popular species are likely to hold lower societal conservation priority [Davies et al, 2018;Donaldson et al, 2017;dos Santos et al, 2020;Jarić et al, 2019], which raises concerns for threatened species which do not enjoy a high or positive public profile [Donaldson et al, 2017]. As a result, communicating the conservation needs of a diversity of taxa to the general public is becoming increasingly important in order to foster engagement with and support for these species [Davies et al, 2018;Jarić et al, 2019;McClain, 2019;Rose, Hunt and Riley, 2018;Velasco et al, 2015]. Takahashi and Tandoc [2016] found that people with an existing interest in science prefer to use the Internet to seek information, with this medium displacing traditional sources of science information such as news media, books and museums.…”
mentioning
confidence: 99%